Overexpression of Gli1 in cancer interstitial tissues predicts early relapse after radical operation of breast cancer - Li, Ying-Hua; Gao, Hai-Feng; Wang, Yan; Liu, Fang; Tian, Xiao-Feng; Zhang, Yang (Chinese Journal of Cancer Research; Vol 24, No 4 (December 07, 2012): Chinese Journal of Cancer Research, 2012)
Objective: In this study, we investigated whether Gli1 expression is important in relapse after radical operation of breast cancer. Methods: Using immunohistochemistry (IHC), Gli1 expression was analyzed in human primary breast cancer (n=284) and the paracancerous tissues (n=20), and also in the local lymph nodes (n=28) and metastatic lymph nodes (n=28). Results: Initial analysis of Gli1 expression in a small cohort of 20 breast tumors and their paracancerous tissues showed a tendency towards Gli1 overexpression in breast cancer tissues (P